Implementation of the V-Model Method in Developing a Web-Based Employee Payroll Accounting Information System - Hellyana, Corie Mei; Rosanah, Mila; Nur Amaliyah, Audy; Argarini Pratama, Eva (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
SMK An-Nur Slawi is one of the private vocational schools located in the Tegal Regency. Currently, the process of managing data and calculating employee salaries at the school is still done manually using Microsoft Excel. This manual method has a fairly high risk of error and requires a relatively long time to complete. Given the importance of managing accurate and efficient financial information in supporting decision-making, an integrated accounting information system is needed to manage financial transaction data more optimally. This study aims to develop a computer-based employee payroll information system by applying the V-Model method in the software development stage. The V-Model method was chosen because it can ensure the verification and validation process at each stage of development so it is expected to improve the quality of the resulting system. The purpose of this study is to implement an automated payroll system that can reduce the error rate in salary calculations, speed up the payroll administration process, and increase the accuracy of employee data recording. With the implementation of this system, it is expected that the payroll process that previously took a relatively long time can be completed in a faster time and the error rate in salary calculations can be minimized. Currently, the employee payroll information system has been successfully designed and is in the trial stage. Interim results show an increase in efficiency in the payroll process, as well as a significant decrease in data input errors compared to the manual method used previously.